AIGC 与传统动画的叙事表达研究:以《致亲爱的自己》与《蘑菇》为例 = Research on narrative expression of AIGC and traditional animation: a case study of "To Dear Me" and "MUSHROOM" - 吴艾妮 Wu, Ai Ni (Nanyang Technological University, 2025)
2022 年 11 月 30 日，人工智能研究公司 OpenAI 发布一款名为“ChatGPT 3.5”的 聊天机器人程序，自此在全球范围内掀起人机交互的全新时代热潮。人类对信息的收 集、处理、创造等方式逐渐发生改变，生成式人工智能——AIGC(Artificial Intelligence Generated Content)正迅速渗透并影响着艺术、人文、影视等多方领域的发 展。AIGC 技术在影视行业的萌芽催生了一系列人机合作完成的影音作品。随着人工 智能技术的飞速迭代，电影节等相关奖项评选活动纷纷增设 AIGC 栏目，将这一新兴 领域的作品纳入专项评选范畴，预示着影视行业的革新性发展。 本文将从“文图学”视角出发，以 AIGC 动画短片《致亲爱的自己》与传统动 画短片《蘑菇》作为主要研究对象，对比二者叙事表达之异同:旨在通过分析叙事结 构与视觉表达，探讨 AIGC 技术对传统影视表达的传承与挑战，从而展望 AIGC 技术 与人为创作协同发展的潜在可能性。 研究发现，AIGC 不仅在技术方面具有显著优势，其在拓展全新美学体验方面 同样具有创新性贡献。然而，尽管 AIGC 的出现降低了创作者门槛，其技术的实用性 却仍有所不足。与此同时，普通创作者与专业从业者之间存在较大的技术认知差距， 普通用户需要进一步接受相关教育或培训，否则难以跨越逐渐加剧的数字鸿沟。 On November 30, 2022, OpenAI released a chatbot program called "ChatGPT 3.5," marking a new era of human-computer interaction. This technology is gradually transforming how humans collect, process, and create information. Artificial Intelligence Generated Content (AIGC) is affecting and reshaping various areas, such as arts, humanities, as well as the film industry. The rise of AIGC in filmmaking has been prompting a range of productions that are assisted by AI technology. With advancements being made in AI, film festivals across the globe have begun to introduce specific categories for AIGC works, bringing them into the official competitions. This signals a major shift in the industry. This study examines the differences between AIGC animation and traditional hand-drawn animation from the perspective of "text and image studies." It focuses on two short films: To Dear Me (AIGC animation) and MUSHROOM (traditional animation). By comparing their narrative structure and visual expression, this study explores how AIGC inherits and challenges traditional filmmaking techniques. It also considers the potential for collaboration between AI technology and human creativity. Findings show that AIGC not only offers technical advantages but also contributes to expanding new aesthetic experiences. However, despite lowering the barrier for creators, its practicality still has certain limitations. Additionally, there is a significant gap in technical knowledge between ordinary creators and professional practitioners. Ordinary creators need to receive further education or training, otherwise they will struggle to bridge the increasingly widening digital divide.